2013
DOI: 10.5755/j01.sace.3.4.4375
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostics and Problems Analysis of Buildings Air Tightness

Abstract: Constantly increasing prices of energy and rising heating costs are forcing inhabitants of multifamily apartment houses and individual houses to think about savings of heating costs and improvement of living conditions as well. Air tightness is one of the most important factors influencing comfortable, energy efficient living environment. During winter time, air movement forms because of the pressure difference between outside and inside air. Air moves from the higher to the lower pressure zone, i. e. cold out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Levinskyte et al, (2016) showed that when effective solutions for linear thermal bridges are used, the same energy efficiency of the building can be reached using less thermal insulating layers and windows and doors of a lower thermal behaviour, if a building with better energy characteristics is designed. The existing situation of airtightness of the building envelope is often not sufficient (Banionis et al, 2013). Better information about effective energy performance measures helps design and construct buildings with a smaller performance gap.…”
mentioning
confidence: 99%
“…Levinskyte et al, (2016) showed that when effective solutions for linear thermal bridges are used, the same energy efficiency of the building can be reached using less thermal insulating layers and windows and doors of a lower thermal behaviour, if a building with better energy characteristics is designed. The existing situation of airtightness of the building envelope is often not sufficient (Banionis et al, 2013). Better information about effective energy performance measures helps design and construct buildings with a smaller performance gap.…”
mentioning
confidence: 99%